The making of China and India in the 21st Century: Long-run human capital a accumulation from 1900 to 2020 - Nitin Kumar Bharti; Yang Li (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We construct a novel dataset of human capital accumulation in China and India from 1900 to 2020 by combining historical records and educational reports to analyze the role of education in economic divergence. Three key findings emerge. First, China pursued a bottom-up strategy, first expanding primary education, followed by secondary and tertiary levels. India, in contrast, adopted a top-down approach, gradually expanding its educational system but prioritizing secondary and higher education before primary. Second, China prioritized quantity over quality, whereas India's expansion attempted to balance quality through teachers' emoluments. Third, China's system features more diversified secondary and tertiary education, with a strong emphasis on vocational education and engineering than India. We highlight the role of educational policies in shaping these trajectories. Our findings on differences in the human capital accumulation in India and China have significant economic implications: education inequality (gini) is not only higher in India but also accounts for a larger share of wage inequality in India (25%), compared with less than 12% in China. Despite a larger share of tertiary-educated graduates, India also struggles with high illiteracy, possibly impeding structural transformation by confining many to the low-productivity agricultural sector. In contrast, China's approach created a larger share of primary, secondary, and vocational graduates combined with more tertiary-educated engineers, generating human capital that is more suitable for the manufacturing sector. India's focus on humanities and accounting in tertiary education fueled service sector growth. Overall, our findings illustrate the importance of human capital composition in shaping long-run economic development.
Keywords: D31; E02; E24; H52; I2; N30; 330; human capital accumulation; education; long run development; inequality; China; India